Microalgae based biorefinery: evaluation of oil extraction methods in terms of efficiency, costs, toxicity and energy in lab-scale (2013)
AbstractSeveral alternatives of microalgal metabolites extraction and transformation are being studied for achieving the total utilization of this energy crop of great interest worldwide. Microalgae oil extraction is a key stage in microalgal biodiesel production chains and their effciency affects signifcantly the global process  effciency.  In  this  study,  a  comparison  of  fve  oil  extraction methods  in  lab-scale was made taking as additional parameters, besides extraction effciency,  the costs of method performing, energy requirements, and toxicity of solvents used, in order to elucidate the convenience of their incorporation to a microalgae-based topology of biorefnery. Methods analyzed were Solvent extraction assisted with high speed homogenization (SHE), Continuous refux solvent extraction (CSE), Hexane based extraction (HBE), Cyclohexane based extraction (CBE) and Ethanol-hexane extraction (EHE), for this evaluation were used the microalgae strains Nannochloropsis sp.,  Guinardia sp.,  Closterium sp.,  Amphiprora  sp. and Navicula  sp., obtained from a Colombian microalgae bioprospecting. In addition, morphological response of strains to oil extraction methods was also evaluated by optic microscopy. Results shows that although there is not a unique oil extraction method which excels in all parameters evaluated, CSE, SHE and HBE appears as promising alternatives, while HBE method is shown as the more convenient for using in lab-scale and potentially scalable for implementation in a microalgae based biorefnery.Keywords: biorefnery, microalgae, oil extraction, sustainability.   Biorefinería basada en microalgas: evaluación de métodos de extracción de aceite en términos de eficiencia, costos, toxicidad y energía a escala laboratorioResumenDistintas alternativas de extracción y transformación de metabolitos de biomasa de microalgas están siendo estudiadas para lograr el aprovechamiento total de este cultivo energético. La extracción del aceite de microalgas es una etapa clave en cadenas de producción de biodiesel a partir de ellas y su  efciencia  afecta  signifcativamente  la  efciencia  global  del  proceso. En  este  estudio  se  realiza  la comparación de cinco métodos de extracción de aceite de microalgas a escala laboratorio, tomando como  criterios  adicionales  a  la  efciencia  de  extracción,  los  costos  de  ejecución  de  cada  método, requerimientos energéticos y toxicidad de los solventes utilizados, con el fn de defnir la conveniencia de su incorporación en una topología de biorefnería a partir de microalgas. Los métodos analizados fueron extracción con solvente asistida con homogenización (SHE), extracción con refujo continuo de solvente (CSE), extracción con hexano (HBE) y ciclohexano (CBE), y extracción de aceite utilizando la mezcla etanol-hexano (EHE). Se emplearon las microalgas de bioprospección nacionalNannochloropsis sp., Guinardia sp., Closterium sp., Amphiprora sp. y Navicula sp. Adicionalmente, se estudió la respuesta morfológica de las cepas mencionadas a los distintos métodos de extracción por medio de microscopía óptica. Los resultados muestran que aunque no hay un método que sobresalga en todos los parámetros evaluados, los métodos CSE, SHE y HBE se perflan como promisorios, mientras que el método HBE se muestra como el más conveniente para utilizar a escala laboratorio en términos generales y potencialmente escalable para su implementación en una biorefnería basada en microalgas.Palabras clave: biorefnería, microalgas, extracción de aceite, sostenibilidad.